Pengawasan pelaksanaan tugas guru di SMK negeri se-kota Solok - Amalia S, Adinda; Marsidin, Sufyarma (Global Action and Education for Society, 2023)
This research aims to find out how to supervise the implementation of teacher duties in State Vocational Schools throughout Solok City in terms of aspects of Learning Planning, Learning Implementation, Implementation of Learning Evaluation, and Implementation of Follow-up Programs. This research is quantitative descriptive. The research population was 242 State Vocational School Teachers in Solok City and a sample of 154 people using proportional stratified random sampling techniques. The data collection instrument was a Likert scale model questionnaire. It can be concluded that Supervision of the Implementation of Teacher Duties in State Vocational Schools throughout Solok City is in the good category with an average score of 4.21. Based on these results, the author suggests that supervision of the implementation of teacher duties at State Vocational Schools in Solok City can be maintained and needs to be improved again so that a conducive learning process is created and learning objectives can be achieved